Examining smartphone use among older adults in Singapore: a screenomics approach - Su, Yifei (Nanyang Technological University, 2024)
This study employed Screenomics—a novel screen-capture methodology to investigate mobile phone behaviors among older adults in Singapore, aiming to elucidate the relationships between phone usage patterns and mental well-being. While Screenomics had been previously applied to observe people’s phone usage such as adolescents and adults, this research pioneered its application among the elderly demographic, examining the nexus between mobile phone use and mental health in older adults. The objective of the research is to use the approach of Screenomics to scrutinize disparities in smartphone usage among older adults in Singapore, focusing on mental well-being to find out the relations between mobile phone use and mental health. A comprehensive dataset comprising 361,280 screenshots was gathered from March to May 2023, involving 30 participants aged 50 and above in Singapore.